Small RNA Profiles of Serum Exosomes Derived From Individuals With Latent and Active Tuberculosis - Lyu, Lingna; Zhang, Xiuli; Li, Cuidan; Yang, Tingting; Wang, Jinghui; Pan, Liping; Jia, Hongyan; Li, Zihui; Sun, Qi; Yue, Liya; Chen, Fei; Zhang, Zongde (Frontiers in Microbiology, 2019)
Tuberculosis (TB) has been the leading lethal infectious disease worldwide since 2014, and about one third of the world’s population has latent TB infection (LTBI). It is largely attributed to the difficulties in diagnosis and treatment of TB and LTBI patients. Exosomes offer a new perspective on investigation of the process of TB infection. In this study, we performed small RNA sequencing to explore small RNA profiles of serum exosomes derived from LTBI and TB patients and healthy controls (HC). Our results revealed distinct miRNA profile of the exosomes in the three groups. We screened 250 differentially expressed miRNAs including 130 specifically expressed miRNAs. Some miRNAs were further validated to be specifically expressed in LTBI (hsa-let-7e-5p, hsa-let-7d-5p, hsa-miR-450a-5p, hsa-miR-140-5p) and TB samples (hsa-miR-1246, hsa-miR-2110, hsa-miR-370-3P, hsa-miR-28-3p, hsa-miR-193b-5p). Besides, we demonstrated four expression panels in LTBI and TB groups, and six expression patterns among the three groups. These specifically expressed miRNAs and differentially expressed miRNAs in different panels and patterns provide potential biomarkers for detection/diagnosis of latent and active TB using exosomal miRNAs. Additionally, we also discovered plenty of small RNAs derived from genomic repetitive sequences, which might play roles in host immune responses along with Mtb infection progresses. Overall, our findings provide important reference and improved understanding about miRNAs and repetitive region-derived small RNAs in exosomes during the Mtb infectious process, and facilitate the development of potential molecular targets for detection/diagnosis of latent and active tuberculosis.